Projeto preliminar de estrutura cm suporte para ferramenta de clinching utilizada no processo de união de chapas por conformação à frio (UCCF) - Gambatto, João Victor Migliavacca (2019)
The discharge of grains into storage silos is currently done through cup elevators, these consist of a vertical structure of empty square metallic modules containing in their interior a mat with containers in parallel, this mat driven by electric motor at the top of the structure, collects and distributes the grains. The form of construction of these modules is by means of two metal sheets, one straight and the other in "U" profile form, these two sheets are commonly joined through MIG welding, a process that generates heat, toxic gases, the material for welding needs to be reseted and the whole process of fixing the plates consists of making welding points, and above these points, continuous welding along the joining of the plates. An alternative to welding is the use of cold conformation sheet union, commercially known as clinching, that consists of pressing a punch against a die, both of them with specific geometries, using a hydraulic actuator as a tool, where the startup of the operation is enough with the push of a button, the process does not need technical skill as welding, nor require material addition or extensive maintenance. The present work aims to design a structure that supports cold forming equipment and enables any industrial operator to complete the production of structural modules of lifts. For this, the methodology of project development was used, more specifically its design phase, which consisted of an informational, conceptual and preliminary project. As a result we obtained the final design model in 3D CAD design software, its dimensions and specified technical drawings, assembly and operating manuals of the structure and simplified budget of the needed material and equipment.